Agrobacterium rhizogenes-mediated genetic transformation of Musa acuminata cv. Vaibalhla (AAA) - Hrahsel, Lalremsiami; Thangjam, Robert (Plant Science Today, 2022)
Agrobacterium rhizogenes-mediated genetic transformation of Musa acuminata cv. Vaibalhla (AAA) was successfully carried out using A. rhizogenes strain A4 harboring the binary vector pCAMBIA2301with VrNHX1gene. In the study, male flowers of M. acuminata cv. Vaibalhla were used as explants to obtain white bud-like structures by culturing on MS basal medium supplemented with 2 mg/l 6-Benzylaminopurine (BAP) and 0.5 mg/l 1-Naphthaleneacetic acid (NAA). The subsequent shoot induction and plantlet regeneration were carried out in MS medium supplemented with Kinetin (2 mg/l) and NAA (0.5 mg/l). For the genetic transformation, in vitro raised plantlets were inoculated with A. rhizogenes strain A4 harboring pCAMBIA2301VrNHX1 for 30 min followed by 2 days of co-cultivation in the dark in a semi solid MS basal medium. The treated plants were then transferred and maintained in MS basal medium supplemented with ascorbic acid (75 mg/l), kanamycin (150 mg/l) and cefotaxime (400 mg/l). Initiation of hairy roots were observed within 2 days of transfer which were evaluated for GUS activity and the subsequent GUS+ roots were assayed for transient transformation by PCR using nptII and NHX1 gene specific primers. The transfer of the plasmid as well as the gene was confirmed with positive bands observed at 540 bp and 1.6 kb respectively.